Prevalence of Sarcocysts in Tongue and Oesophagus of Dromedary Camels from Bikaner district of Rajasthan# - Asopa, Shesh; Joshi, A.; Dadhich, H.; Vyas, I. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The prevalence of Sarcocysts was investigated by histopathological examination of 80 tongue and esophagus samples collected from  camel (Camelus dromedarius) irrespective of age, sex and breed during July 2017 to June 2018 from Bikaner district of Rajasthan. The infection rates of Sarcocysts in the tongue and esophagus was 5 per cent (4 of 80) and 6.25 per cent (5 of 80), respectively. Histopathologically, different sized dark stained sarcocysts in between muscle bundles of tongue and esophagus were seen along with mild cellular infiltration mainly of eosinophilic granulocytes surrounding the lesion. The tissue response to Sarcocysts was minimal and reaction to the cysts caused tissue damages resulting in congestion, haemorrhages, mononuclear cells infiltration, necrotic changes and fibrosis. On the basis of overall findings it can be stated that Sarcocysts infection rate in camels can be massive and the cysts may remain in situ for a long time.
Keywords: Camel; Sarcocysts; Histopathology; Rajasthan